2010
DOI: 10.1063/1.3533808
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nickel germanide contacts to Ge nanowires

Abstract: Nickel germanide contacts are expected to play an important role in Ge-based electronics similar to that of their nickel silicide counterparts in Si devices. Here we have studied the solid state reaction between Ni contact pads and Ge nanowires. We observe the formation of axial nickel germanide segments after annealing at temperatures as low as 300 °C for 2 min. The nickel germanide segments are polycrystalline, without an epitaxial relationship to the Ge nanowire, in contrast to observations of epitaxial nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
1
31
0
1
Order By: Relevance
“…In the case of the SiGe NW with no compressive induced during annealing, as opposed to the formation of SiGe grains between Ni‐germanosilicide grain boundaries, a void was formed instead. In fact, our observation are more in line with the study of Ni germanide formation in Ge NW, where a break in the Ge NW near the Ni germanide–Ge interface was always observed at temperatures >450 °C . It is more reasonable to propose that in the case of SiGe NW without any compressive stress induced during annealing, the Ge atoms in the SiGe NW have a tendency to segregate toward the Ni‐germanosilicide–Ni source interface.…”
Section: Resultssupporting
confidence: 89%
“…In the case of the SiGe NW with no compressive induced during annealing, as opposed to the formation of SiGe grains between Ni‐germanosilicide grain boundaries, a void was formed instead. In fact, our observation are more in line with the study of Ni germanide formation in Ge NW, where a break in the Ge NW near the Ni germanide–Ge interface was always observed at temperatures >450 °C . It is more reasonable to propose that in the case of SiGe NW without any compressive stress induced during annealing, the Ge atoms in the SiGe NW have a tendency to segregate toward the Ni‐germanosilicide–Ni source interface.…”
Section: Resultssupporting
confidence: 89%
“…Instead, different germanide phases have been identified at the germanide/germanium interface. Dellas et al [46], annealed Ni contact pads over Ge NWs for 2 min at temperatures ranging between 300 and 400 • C and found that the germanide phase is independent of the growth direction, similar to the case of Si [47]. They used selected area electron diffraction (SAED) in TEM to identify the hexagonal lattice constants of polycrystal NiGe x : a = 3.95Å and c = 5.187Å.…”
Section: Nickel Germanide Formationmentioning
confidence: 99%
“…On the other hand, many germanides, such as Mn 5 Ge 3 and Ni 3 Ge, exhibit ferromagnetism above room temperature [20,21], and thus offer great advantages over silicides for future applications in spintronics, such as realizing spin injection into semiconductor from a ferromagnetic contact. Therefore, there is an increasing research interest on the metal-Ge nanowire system, such as Ni-Ge [13][14][15] and Cu-Ge [16][17][18]. For comparison, Table 1 briefly summarizes the literature report of Si and Ge nanowire heterostructures formed by solid-state reactions between a semiconductor nanowire and metal contacts.…”
Section: Introductionmentioning
confidence: 99%